2013
DOI: 10.1016/j.rmed.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Marine lipid fraction PCSO-524™ (lyprinol®/omega XL®) of the New Zealand green lipped mussel attenuates hyperpnea-induced bronchoconstriction in asthma

Abstract: PCSO-524 (Lyprinol)/Omega XL) may have beneficial effects in HIB and asthma by serving as a pro-resolving agonist and/or inflammatory antagonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 52 publications
5
44
0
2
Order By: Relevance
“…Our study [15] supports a number of other studies that have shown Ô is effective in treating human asthma [16] and allergic inflammation and lung function using a murine model of ovalbumin-induced allergic airway disease [17]. Since the levels of EPA and DHA in our study [15], and the Emelyanov et al [16] study, using PCSO-524 Ô were very low, the physiological mechanism(s) behind the attenuation in airway inflammation and improvement in lung function are unclear. The potent anti-inflammatory action of PCSO-524 Ô may be due to the fact that this extract contains up to 91 fatty acid components, and contains furan acids, which have been shown to possess more potent antiinflammatory activity than EPA [18].…”
Section: Pcso-524supporting
confidence: 80%
See 1 more Smart Citation
“…Our study [15] supports a number of other studies that have shown Ô is effective in treating human asthma [16] and allergic inflammation and lung function using a murine model of ovalbumin-induced allergic airway disease [17]. Since the levels of EPA and DHA in our study [15], and the Emelyanov et al [16] study, using PCSO-524 Ô were very low, the physiological mechanism(s) behind the attenuation in airway inflammation and improvement in lung function are unclear. The potent anti-inflammatory action of PCSO-524 Ô may be due to the fact that this extract contains up to 91 fatty acid components, and contains furan acids, which have been shown to possess more potent antiinflammatory activity than EPA [18].…”
Section: Pcso-524supporting
confidence: 80%
“…Recently, our laboratory [15] examined the therapeutic potential of a different form of marine oil (PCSO-524 Ò ; LyprinolÔ/ Omega XLÔ), a patented extract of stabilized lipids from the New Zealand green lipped mussel, Perna canaliculus, in treating airway inflammation and HIB in asthmatic patients.…”
mentioning
confidence: 99%
“…6,18 The most obvious diff erence is that we used inhaled mannitol, a bronchial provocation challenge that has been derived from the understanding of the eff ects of dry air hyperpnea-induced BHR, which is a well-established alternative challenge stimulus to study EIB. There is strong evidence that the airway response to mannitol closely mimics central components of EIB, such as the activation of mast cells and eosinophils, resulting in the release of bronchoconstrictive mediators.…”
Section: Discussionmentioning
confidence: 99%
“…This marine oil lipid and n -3 PUFA blend is a multifarious mixture of sterol esters, sterols, polar lipids, triglycerides, EPA and DHA (split between the triacylglycerol and polar lipid classes), and free fatty acids [24], and has been shown to exert its anti-inflammatory effects via furan fatty acids [25], and inhibition of cyclooxygenase (COX)-2 and 5-lipoxyeganse (LOX) pathways for the metabolism of arachidonic acid, thereby leading to a subsequent reduction in pro-inflammatory leukotriene, prostaglandin, and cytokine production from inflammatory cells [22,26]. A number of human and animal studies have shown that the green-lipped mussel oil blend may have beneficial effects in treating inflammatory diseases such as osteoarthritis, rheumatoid arthritis, inflammatory bowel disease, asthma [22], and exercise- induced bronchoconstriction [27]. These preliminary findings support the potential for supplementation with the green-lipped mussel oil blend in order to attenuate muscle damage and inflammation that can occur following muscle damaging exercise.…”
Section: Introductionmentioning
confidence: 99%